1998
DOI: 10.1152/jn.1998.80.3.1456
|View full text |Cite
|
Sign up to set email alerts
|

Spike-Wave Complexes and Fast Components of Cortically Generated Seizures. II. Extra- and Intracellular Patterns

Abstract: In the previous paper we have demonstrated, by means of field potential and extracellular unit recordings, that bicuculline-induced seizures, which include spike-wave (SW) or polyspike-wave (PSW) complexes, are initiated intracortically and survive ipsilateral thalamectomy. Here, we used multisite field potential and extracellular recordings to validate the patterns of cortical SW/PSW seizures in chronically implanted, behaving cats. To investigate the cellular patterns and excitability during spontaneously oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(107 citation statements)
references
References 60 publications
11
96
0
Order By: Relevance
“…2A), and thus the rapid monosynaptic excitation of CLs, together with post-inhibitory rebound potentials, probably induced through interneurons, explain the synchronization observed between the "spike" of the ECoG and the gross lemniscal activity ( Figs 7B, 8C, left panel). It has been demonstrated that the fast-rhythmic bursting cortical neurons contribute to the initiation of spontaneous and electrically elicited spike-and-wave cortical paroxysms, 44 and since the axons of these cells reach the cuneate (Fig. 2B), they might be responsible for the initial powerful excitatory effects exerted by the cerebral cortex on CLs, as reported previously.…”
Section: Spread Of Cortical Paroxysmssupporting
confidence: 76%
“…2A), and thus the rapid monosynaptic excitation of CLs, together with post-inhibitory rebound potentials, probably induced through interneurons, explain the synchronization observed between the "spike" of the ECoG and the gross lemniscal activity ( Figs 7B, 8C, left panel). It has been demonstrated that the fast-rhythmic bursting cortical neurons contribute to the initiation of spontaneous and electrically elicited spike-and-wave cortical paroxysms, 44 and since the axons of these cells reach the cuneate (Fig. 2B), they might be responsible for the initial powerful excitatory effects exerted by the cerebral cortex on CLs, as reported previously.…”
Section: Spread Of Cortical Paroxysmssupporting
confidence: 76%
“…LFPs were analyzed by the wave-triggered average (WTA) technique (Steriade et al, 1998) and the fast Fourier transform algorithm. An oscillation index was computed as peak amplitude divided by total power.…”
Section: Methodsmentioning
confidence: 99%
“…Neocortical oscillations at ϳ10 Hz are observed in vivo and in brain slices under conditions of enhanced excitability (Silva et al, 1991;Flint and Connors, 1996;Lukatch and MacIver, 1997;Steriade et al, 1998b;Castro-Alamancos, 2000, 2006Castro-Alamancos and Rigas, 2002;Castro-Alamancos et al, 2007). Oscillations at 10 Hz occur while GABA receptors are blocked (Flint and Connors, 1996), suggesting that they are generated by the excitatory network.…”
Section: Implications For Epilepsymentioning
confidence: 99%